Q-3 (b) may i know the answer of my question
Attachments:
![](https://hi-static.z-dn.net/files/d93/61b97e77b07e23df2148e05b9c2d9035.jpg)
Answers
Answered by
0
cos11°+sin11°
=cos(90°-79°)+sin11° [∵, cos(90°-Ф)=sinФ]
=sin79°+sin11°
=2sin(79°+11°)/2cos(79°-11°)/2 [∵, sinC+sinD=2sin(C+D)/2cos(C-D)/2]
=2sin45°cos34°
=2×1/√2×cos(90°-56°)
=√2sin56° (Proved)
=cos(90°-79°)+sin11° [∵, cos(90°-Ф)=sinФ]
=sin79°+sin11°
=2sin(79°+11°)/2cos(79°-11°)/2 [∵, sinC+sinD=2sin(C+D)/2cos(C-D)/2]
=2sin45°cos34°
=2×1/√2×cos(90°-56°)
=√2sin56° (Proved)
Similar questions
Environmental Sciences,
9 months ago
Political Science,
9 months ago
Computer Science,
9 months ago
Math,
1 year ago
Physics,
1 year ago
Geography,
1 year ago
Geography,
1 year ago